Improving the efficiency of a sowing technology based on the improved structural parameters for colters - Nanka, Alexander; Morozov, Ivan; Morozov, Vladimir; Krekot, Mykola; Poliakov, Anatolii; Kiralhazi, Ivan; Lohvynenko, Mykhailo; Sharai, Konstantin; Babiy, Andriy; Stashkiv, Mykola (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports results from research into improving the efficiency of the technological process of sowing agricultural crops based on the theoretical and experimental studies of functional dependences of operations in the course of the technological process on parameters for colters. Their variants have been substantiated, which, in the subsequent synthesis in various combinations, has made it possible to construct, depending on the requirements, a family of versatile, combined, and specialized colters. Based on the comparison of analysis and experimental research into the widely applied designs of colters, as well as the parameters for their operation, we have discovered flaws in operation and established their impact on reducing the yield of grain crops. In addition, we have theoretically substantiated the influence of the type and structure of colters on the interaction with soil and seeds during sowing under different conditions. That has made it possible to establish a correlation between the parameters for colters and operations within the technological process. The data obtained have become the basis for designing new structural elements and types of colters (a family of them) that meet the requirements of the agronomic science and consumers. They improve the technological processes of interaction between their structural parameters (frontal surface, tip, side cheeks) and soil. This improves the formation of furrow for seeds, arranging them evenly for area and depth of covering with moist soil. That improves the germination, development of cultural plants, and increases yields by up to 10 %. These working bodies are capable of row, narrow-row, scattered, anti-erosion planting, as well as sowing sparse shoots; they improve productivity and protect soil from erosion. Thus, the result of the current work is the created and improved family of colters for grain seeders: – with universal tips: a tip colter, an anchor colter, a tip colter with a combined tip, a colter with a combined tip, a colter with a combined tip with cutouts in cheeks and a soil compactor-separator, a tip colter with a guider and adjustable seed reflector; – for narrow rows: a tip colter; – combined: a combined tip colter with a right angle of soil penetration with a guider and a seed reflector; – anti-erosion: a tip colter, an anchor-disk colter with an attachment mechanism, a paw colter.